Methanol electrooxidation on core-shell Ag@Pdx catalysts - Xiaobo Yang; Xili Tong; Xingchen Liu; Kaixi Li; Nianjun Yang (Electrochemistry Communications, 2021)
The performance of a direct methanol fuel cell (DMFC) is strongly dependent on the catalytic anode. A high-performance anode is expected to offer enhanced intrinsic activity and/or a large electrochemical surface area. Herein, a series of Ag-core/Pd-shell (Ag@Pdx, x = 1,3,5) catalysts are synthesized in which the thickness of the Pd shell is varied. Both tensional strain and electron transfer between the Ag core and the Pd shell are found to affect the intrinsic activity of these Ag@Pdx catalysts. Of these, the Ag@Pd3 catalyst exhibits the best performance for the methanol oxidation reaction (MOR), showing 4.1 times higher mass activity and 2.6 times higher specific activity than a Pd/C catalyst. Furthermore, density functional theory calculations show that this high MOR performance stems from a stronger adsorption of CH3OH and OH on the Pd active sites. This catalyst is thus a promising candidate for inclusion in a high-performance DMFC.